Promoting Privacy, Fairness, and the Open Court Principle in Immigration and Refugee Proceedings - Khan, Jon; Rehaag, Sean (Ottawa Law Review / Revue de droit d’Ottawa)

(untitled) (Ottawa Law Review / Revue de droit d’Ottawa, 2022)
Court decisions and documents are becoming easier to access online, and this access provides many benefits. Access to legal data is a key driver of technological innovations that may advance access to justice. However, because court decisions and documents often contain personal information, increased access leads to serious privacy concerns.The Federal Court has demonstrated leadership among Canadian courts in proactively grappling with these issues in considering increased electronic access to court records. To date, stakeholder consultations highlighted immigration and refugee proceedings as a concerning area for privacy risks. Some have called for severe restrictions on access to court documents in those proceedings, while others contend that the open court principle must always trump privacy.We write this article to offer a case study of access to immigration and refugee law court documents — which we acknowledge is a hard case — to think through what fair access to court materials should look like as we enter the era of computational law. We suggest that debates too quickly accept irreconcilable tensions between privacy and the open court principle: stakeholders often just assert that one or the other should take precedence. Rather than a limited framework that focuses on privacy and openness as binary opposites, we argue for prioritizing fair access to court materials. This approach offers a way out of the impasse between positions that rank either privacy or openness ahead of the other. It also ensures that access limits do not amplify information asymmetries that disadvantage refugees and other displaced people.